The choice to empower your health. - Botts, Stephanie (RDH (0279-7720), 2022)
Dental clinicians are at high risk for musculoskeletal disorders (MSDs). Up to 96% of dental hygienists report pain due to clinical work habits, including repetitive movements, bending, twisting, reaching, incorrect operator and patient positioning, and a static posture. Ergonomics is the science of fitting the working environment to the practitioner, instead of forcing one's body to acclimate to the environment. Practicing proper ergonomics can increase productivity, decrease pain, and lengthen one's career. At the conclusion of this course, participants will learn ergonomic techniques, exercises, proper patient positioning, and equipment choices to allow them to practice pain free.